Dampak Indeks Nikkei 225, Indeks Dow Jones, Suku Bunga FED, dan Inflasi Terhadap IHSG - M Rifki Bakhtiar; Tri Purwani (Journal of Economics and Business, 2021)
The focus of this study is to analyze the impact of the movement of the Nikkei 225 Index, the Dow Jones Index, Fed Interest Rates, and Inflation on the JCI. Determination of the sample in this study using a saturated sampling method with a total of 60 samples. The data obtained were analyzed using multiple linear regression analysis techniques with the SPSS program. Based on the results of the analysis and discussion in this study, the results showed that the Nikkei 225 Index and the Fed Interest Rate had a negative effect on the JCI, while the Dow Jones Index had a positive effect on the JCI. The results of this study also show that inflation has no effect on the JCI. This study provides empirical evidence for investors that the increase in the Composite Stock Price Index is inversely proportional to the Nikkei 225 Index, and Fed interest rates, but directly proportional to the Dow Jones Index. This means that an increase in the Dow Jones Index will be followed by an increase in the JCI, but if an increase in the Nikkei 225 Index and the Fed interest rate will lower the JCI.